Dampak Konversi Hutan Tropis dan Penggunaan Pupuk Kimia terhadap Keanekaragaman Hayati pada Proyek Food Estate Kabupaten Gunung Mas - Vera Desti Puspitasari; Iqbal Aji Saputra; Rayi Kharisma Rajib (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Food Estate is part of the National Economic Recovery (PEN) program aimed at anticipating a food crisis in Indonesia due to the Covid-19 pandemic. The program is supported by the Omnibus Law on Job Creation, which mandates ministers/head of agencies, governors, and regents/mayors to provide the necessary permits and non-permits for the implementation of National Strategic Projects. The research methods used are literature studies, spatial analysis, and the collection of primary data from books, scientific articles, and the internet. The research results indicate that the conversion of tropical forests into Food Estate land has led to the loss of natural habitats, forest fragmentation, and carbon emissions. The excessive use of chemical fertilizers has polluted groundwater and rivers, causing eutrophication and disrupting the balance of ecosystems. The cumulative impact of tropical forest conversion and the use of chemical fertilizers has led to a significant decrease in biodiversity in the Gunung Mas Food Estate area. This research uses the Normative Juridical method, aimed at analyzing and dissecting the components of a problem for further examination and then linking them to the laws, legal principles, and legal norms applicable as a solution to the food estate issue in Gunung Mas Regency. This research recommends the implementation of sustainable farming practices, such as reducing forest conversion, using organic fertilizers, and applying environmentally friendly farming techniques, to minimize the negative impacts on biodiversity and achieve sustainable food security in the Gunung Mas Food Estate.